(untitled) (Analysis in Theory and Applications, 2017)
In this paper, we present a method for constructing multivariate tight framelet packets associated with an arbitrary dilation matrix using unitary extension principles. We also prove how to construct various tight frames for L^2(R^d) by replacing some mother framelets.